Energy-efficient user association mechanism enabling fully hybrid spectrum sharing among multiple 5G cellular operators - Mothana L. Attiah; A. A. Md Isa; Zahriladha Zakaria; Ahmed M. Dinar; M . K. Abdulhameed; Mowafak K. Mohsen (Universitas Ahmad Dahlan, 2019)
Spectrum sharing (SS) is a promising solution to enhance spectrum utilization in future cellular systems. Reducing the energy consumption in cellular networks has recently earned tremendous attention from diverse stakeholders (i.e., vendors, mobile network operators (MNOs), and government) to decrease the CO2 emissions and thus introducing an environment-friendly wireless communication. Therefore, in this paper, joint energy-efficient user association (UA) mechanism and fully hybrid spectrum sharing (EE-FHSS) approach is proposed considering the quality of experience QoE (i.e., data rate) as the main constraint. In this approach, the spectrum available in the high and low frequencies (28 and 73 GHz) is sliced into three portions (licensed, semi-shared, and fully-shared) aims to serve the users (UEs) that belong to four operators in an integrated and hybrid manner. The performance of the proposed QoE-Based EE UA-FHSS is compared with the well-known maximum signal-to-interference-plus-noise ratio (max-SINR UA-FHSS). Numerical results show that remarkable enhancement in terms of EE for the four participating operators can be achieved while maintaining a high degree of QoE to the UEs.